MicroRNA 101b Is Downregulated in the Prefrontal Cortex of a Genetic Model of Depression and Targets the Glutamate Transporter SLC1A1 (EAAT3) in Vitro - Wei, Ya Bin (Oxford University Press, 2016)

(untitled) (Int J Neuropsychopharmacol)
BACKGROUND: MicroRNAs (miRNAs) are small regulatory molecules that cause translational repression by base pairing with target mRNAs. Cumulative evidence suggests that changes in miRNA expression may in part underlie the pathophysiology and treatment of neuropsychiatric disorders, including major depressive disorder (MDD). METHODS: A miRNA expression assay that can simultaneously detect 423 rat miRNAs (miRBase v.17) was used to profile the prefrontal cortex (PFC) of a genetic rat model of MDD (the Flinders Sensitive Line [FSL]) and the controls, the Flinders Resistant Line (FRL). Gene expression data from the PFC of FSL/FRL animals (GEO accession no. GSE20388) were used to guide mRNA target selection. Luciferase reporter assays were used to verify miRNA targets in vitro. RESULTS: We identified 23 miRNAs that were downregulated in the PFC of the FSL model compared with controls. Interestingly, one of the identified miRNAs (miR-101b) is highly conserved between rat and human and was recently found to be downregulated in the PFC of depressed suicide subjects. Using a combination of in silico and in vitro analyses, we found that miR-101b targets the neuronal glutamate transporter SLC1A1 (also known as EAAC1 or EAAT3). Accordingly, both mRNA and protein levels of SLC1A1 were found to be upregulated in the PFC of the FSL model. CONCLUSIONS: Besides providing a list of novel miRNAs associated with depression-like states, this preclinical study replicated the human association of miR-101 with depression. In addition, since one of the targets of miR-101b appears to be a glutamate transporter, our preclinical data support the hypothesis of a glutamatergic dysregulation being implicated in the etiology of depression.